1998
DOI: 10.1111/1468-2311.00096
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Prison Environment upon Inmate Drug Taking Behaviour

Abstract: The aim of the present study was to examine, from an inmate perspective, their use of drugs and the perceived effect of the prison environment upon their drug using behaviour. Design of the study was an analytic survey, presented to the respondents as an anonymous, selfadministered questionnaire. The results suggest that the prison environment is not a supportive environment for those individuals that wish to abstain from drug use and indeed for most respondents, actually encouraged drug use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 6 publications
0
19
0
4
Order By: Relevance
“…They found that the criminal justice system is a reservoir for drug abusers (Leukefeld & Tims, 1993). A substantial proportion of the inmate population continues to use drugs inside prison (Swann & James, 1998).…”
Section: The Treatment Perspective the Prevalence Of Drugs Inside Prisonmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the criminal justice system is a reservoir for drug abusers (Leukefeld & Tims, 1993). A substantial proportion of the inmate population continues to use drugs inside prison (Swann & James, 1998).…”
Section: The Treatment Perspective the Prevalence Of Drugs Inside Prisonmentioning
confidence: 99%
“…In fact, as punishment and incapacitation supplanted rehabilitation and treatment as the dominant themes of modern corrections, the issue of drug use shifted from the domain of criminal justice to that of public health (Swann & James, 1998). Much current research on prison drug use now falls under the auspices of public health and social work rather than criminal justice.…”
mentioning
confidence: 99%
“…A second interpretation, demanding systematic investigation, is that more prisoners are initiating injection, sharing rigs, and contracting HCV/HIV inside prison (Crewe, 2005;Swann & James, 1998). Finally, injection and HCV/HIV rates at this prison might be unchanged or lower than in the past but masked by CSC's practice of reporting data at the level of geographical regions versus individual prisons.…”
Section: Elevated Rates Of Hcv/hiv Seropositivity and Injectorsmentioning
confidence: 96%
“…Also, drug dealing can be part of the inmates' attempt to build personal respect and reputation (Crewe 2006(Crewe , 2009. Studies show that drugs are used strategically by inmates as a kind of self-medication, as a way to cope with imprisonment, and as a means of relieving insomnia and boredom (Boys et al 2002;Swann and James, 1998;Cope, 2003;Ritter et al, 2013;Keene, 1997). Almost no studies, however, have focussed on the experiences and role of prison officers in relation to inmates' drug use (Ritter et al 2013, Carlin 2005.…”
Section: Introductionmentioning
confidence: 99%